2023
DOI: 10.1590/s0004-2803.202302022-96
|View full text |Cite
|
Sign up to set email alerts
|

High-Fiber Diet Promotes Metabolic, Hormonal, and Satiety Effects in Obese Women on a Short-Term Caloric Restriction

Abstract: Background: Several mechanisms, including excessive hunger, account for patients’ difficulties in maintaining weight loss and dietary changes after caloric restriction. Objective: To evaluate the effect of short-term high-fiber calorie-restricted diet in appetite-regulating hormones, and hunger and satiety sensations in women with obesity. Methds: In a randomized controlled trial study, thirty women with body mass index (BMI) higher than 30 kg/m2, and aged from 20 to 50 years were hospitalized following a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…In our laboratory, glucose levels and incremental areas under curve after intake were significantly lower with dietary fiber-enriched brown rice crackers than with white rice crackers [16]. In recent years, it has also been suggested that dietary fiber exerts appetitesuppressing and anti-obesity effects [17]. Sake lees are rich in dietary fiber.…”
Section: Inmentioning
confidence: 99%
“…In our laboratory, glucose levels and incremental areas under curve after intake were significantly lower with dietary fiber-enriched brown rice crackers than with white rice crackers [16]. In recent years, it has also been suggested that dietary fiber exerts appetitesuppressing and anti-obesity effects [17]. Sake lees are rich in dietary fiber.…”
Section: Inmentioning
confidence: 99%